A pilot investigation of differential hydroxymethylation levels in patient-derived neural stem cells implicates altered cortical development in bipolar disorder - Kumar, Ashish; Kos, Mark Z.; Roybal, Donna; Carless, Melanie A. (Frontiers in Psychiatry, 2023)
Bipolar disorder (BD) is a chronic mental illness characterized by recurrent episodes of mania and depression and associated with social and cognitive disturbances. Environmental factors, such as maternal smoking and childhood trauma, are believed to modulate risk genotypes and contribute to the pathogenesis of BD, suggesting a key role for epigenetic regulation during neurodevelopment. 5-hydroxymethylcytosine (5hmC) is an epigenetic variant of particular interest, as it is highly expressed in the brain and is implicated in neurodevelopment, psychiatric and neurological disorders. In this study, we used reduced representation hydroxymethylation profiling (RRHP) to perform genome-wide 5hmC profiling of induced pluripotent stem cells (iPSCs) and neuronal stem cells (NSCs), derived from two individuals with BD and their unaffected siblings (n=4), to model 5hmC changes during neuronal differentiation and assess their impact on BD risk. The majority of profiled sites (68.8%) are located in genic regions (including 5’ and 3’ UTRs and upstream promoter regions). Elevated 5hmC levels were observed for 3' UTRs (~26 mean counts per site for all cell lines) and exons (~24 mean counts per site) and for 2-kb shorelines of CpG islands (~32 mean counts per site). Paired T-tests of normalized 5hmC counts between iPSC and NSC cell lines revealed enrichment of differentially methylated sites within genes associated with plasma membrane (FDR=9.1x10-12), axon guidance (FDR=2.1x10-6), neuron projection (FDR=2.4x10-6) and neuronal cell body (FDR=2.0x10-5), with the top differentially methylated site located within a transcription factor binding site for the KCNK9 gene (P=8.8x10-6), encoding a potassium channel protein involved in neuronal activity and migration. Protein-protein-interaction (PPI) networking showed significant connectivity (P=3.2x10-10), with two major clusters – the first including several genes associated with axon guidance and the second harboring genes associated with ion transmembrane transport. Comparison of BD cases and unaffected siblings revealed enrichment for genes functionally annotated to extracellular matrix (FDR=1.0x10-8), plasma membrane (FDR=5.5x10-5), actin cytoskeleton (FDR=3.1x10-4) and GTPase activator activity (FDR=3.2x10-3). Differential hydroxymethylation was seen in genes such as CUX2 (P=2.4x10-5), a transcription factor that controls neuronal proliferation, dendrite branching and synapse formation, and in the promotor of DOK-7 (P=3.6x10-3), an adaptor protein known to regulate neuromuscular synapse formation.